Setetes Darah, Sejuta Kasih dan Harapan: Kegiatan Donor Darah Sukarela oleh Lions Club Medan Angkasa untuk Meningkatkan Ketersediaan Stok Darah di Medan - Anto, Endy Juli; Tim Lions Club Medan Angkasa; Tambunan, Ronald T. H.; Manullang, Frengky S.; Tiji, Wijaya Taufik; Fauzi, Tengku M.; Sinatra, Jadeny; Jamnasi, Juli; Siahaan, Jekson Martiar (Universitas Methodist Indonesia, 2025)
Blood donation is a critical healthcare activity that saves millions of lives worldwide. This community service activity aimed to increase blood stock availability and raise awareness about voluntary blood donation through Lions Club Medan Angkasa's initiative